Reduced Right Hippocampal Volume on MRI and Correlation with Major Depressive Disorder - Diptya, Ibnu; Yueniwati, Yuyun (Faculty of Medicine, Universitas Airlangga, 2024)
Introductions: Many studies have shown in the field of psychiatry results in specific changes in brain anatomy and function associated with measurable clinical outcomes. One of the biggest difficulties in diagnosing and treating psychiatric disorders is that human behavior involves complex mechanisms when compared to experimental animals. Case: 25-year-old female, diagnosed with Major Depressive Disorder (MDD) 6 months ago at a General Hospital in Malang, Indonesia. The patient felt depressed, had trouble sleeping, and had attempted suicide. MRI of the hippocampus was performed at the power of 3 Tesla magnetic strength (PHILIPS INGENIA 3.0T). MRI data processing and hippocampal volumetric analysis were performed using the volBrain HIPS software. Discussion: The left hippocampus volume was larger than the right volume, with a history of the patient never doing exercise or exercising regularly. In general, the hippocampus can be asymmetrical on both sides and larger on the right side. Although asymmetry in the hippocampus is normal, but there are no studies that say the volume of the left hippocampus is larger than the volume of the right hippocampus in a normal people. Conclusions: a person with depression should be screened and planned for early treatment. In the field of radiology, psychoradiology plays an important role in the main clinical situation in guiding decisions, especially treatment planning, as well as monitoring the results of care carried out in patients with psychiatric disorders.